The Glaciation of Yulungshan, Yunnan, China - Mei-Ngo, Jen (ERDKUNDE, 1958)
Yulungshan (5914 m), located in the northwest of China's Yunnan Province, has a number of small cirque glaciers, some of which send down tongues and form terminus glaciers that find their lower end at about 4500 m N.N.. Two Quaternary glaciations, whose terminal moraines are at 3200 and 2800 m, have been distinguished. They are tentatively referred to here as the Tali and Litchiang glaciations and probably correspond to the Würm and Riss glaciations of the Alps. From the relatively small extent of the Litchiang glaciation, the freshness of the major fault stage, and the occurrence of tropical plants at high altitudes, it is concluded that the main uplift of the Yulungshan probably occurred in the late Quaternary.